Analisis Pendekatan Feminisme Dalam Lagu Rossa Yang Berjudul “Cintai Aku” Dan “Hey Ladies” - Hafni, Suci (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2024)
This research aims to analyze the messages contained in the two songs sung by Rossa, namely Cintai Aku and Hey Ladies using a feminist approach. The method used in this research is a qualitative descriptive method using listening and note-taking techniques. Literary works have several types, one of which is song. Songs are literary works to convey emotional and social messages through song lyrics. These two songs have different views on women's perspectives. The song entitled